2006
DOI: 10.2174/138161206777947498
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Cellular Roles for Novel Protein Kinase C Isoenzymes

Abstract: A number of in vitro studies have implicated protein kinase Cdelta (PKCdelta) and PKCepsilon in the regulation of the immune system. In recent years, this has been convincingly demonstrated in mice deficient for PKCdelta and PKCepsilon. The reported phenotypes for these transgenic mice indicate that PKCdelta suppresses immunoresponsiveness and inhibits the proliferation of B-lymphocytes, while PKCepsilon is required for macrophages to mount an effective immune response to bacterial pathogens. In either case, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
0
18
1
Order By: Relevance
“…3A). Many different PKC isoforms have been identified in mammals (22,23); of these, the α, δ, and ε isoforms are dominantly expressed in BAECs (24). We designed and validated siRNAs to knock down these PKC isoforms ( Fig.…”
Section: H 2 O 2 Induces Marcks Phosphorylation and Translocation Inmentioning
confidence: 99%
“…3A). Many different PKC isoforms have been identified in mammals (22,23); of these, the α, δ, and ε isoforms are dominantly expressed in BAECs (24). We designed and validated siRNAs to knock down these PKC isoforms ( Fig.…”
Section: H 2 O 2 Induces Marcks Phosphorylation and Translocation Inmentioning
confidence: 99%
“…However, many studies have implicated downregulation, rather than activation, of PKCδ in sporadic human colonic cancer in resistance to apoptosis and differentiation [9, 10]. Transient overexpression of PKCδ has been linked to tumor-suppressive functions, including suppression of anchorage-independent cell growth [11], reversal of colonic epithelial cells transformation via Src [12], and inhibition of neoplastic phenotype via p53 [13]. Therefore, PKCδ is thought of as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…PKCδ is also a positive regulator of cell growth. It can function as an antiapoptotic protein and can contribute to cell transformation and metastasis [1, 7, 33, 34]. We have shown that acquisition of resistance by HeLa cells to the chemotherapeutic drug cisplatin was associated with loss of regulation of PKCδ [35, 36].…”
Section: Introductionmentioning
confidence: 99%